Pengaruh Environmental, Social Dan Governance (ESG) Disclosure Terhadap Nilai Perusahaan Di Moderasi Ukuran Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Nafisah; Liyanto (Majalah Ekonomi, 2025)
This study investigates the effect of Environmental, Social, and Governance (ESG) disclosure on firm value and examines whether firm size moderates this relationship. While prior literature indicates that ESG disclosure can enhance firm value through improved legitimacy, corporate reputation, and stakeholder trust, empirical evidence from Indonesia remains mixed and inconclusive. Adopting a quantitative approach, this research analyzes secondary data from 49 non-financial companies listed on the Indonesia Stock Exchange over the 2021–2023 period. The analytical method employed is panel data regression with an interaction term to test moderation effects. The findings reveal that none of the ESG dimensions—environmental, social, or governance disclosures—significantly affect firm value. Furthermore, firm size does not moderate the relationship between ESG disclosure and firm value. These results suggest that Indonesian investors have not yet fully integrated ESG information into their investment decisions, and that larger firms do not necessarily benefit from greater ESG transparency. This study contributes to the ESG literature in emerging markets by highlighting the influence of institutional context and domestic market perception in shaping the impact of ESG practices. The practical implication underscores the need for firms to enhance the quality and relevance of their ESG disclosures in order to create long-term stakeholder value.